Speech Recognition Application for the Speech Impaired using the Android-based Google Cloud Speech API - Nenny Anggraini; Angga Kurniawan; Luh Kesuma Wardhani; Nashrul Hakiem (Universitas Ahmad Dahlan, 2018)
Those who are speech impaired (tunawicara in the Indonesian language) suffer from abnormalities in their delivery (articulation) of the language as well their voice in normal speech, resulting in difficulty in communicating verbally within their environment. Therefore, an application is required that can help and facilitate conversations for communication. In this research, the authors have developed a speech recognition application that can recognise speech of the speech impaired, and can translate into text form with input in the form of sound detected on a smartphone. By using the Google Cloud Speech Application Programming Interface (API), this allows converting audio to text, and it is also user friendly to use such APIs. The Google Cloud Speech API integrates with Google Cloud Storage for data storage. Although research into speech recognition to text has been widely practiced, this research try to develop speech recognition, specially for speech impaired's speech, as well as perform a likelihood calculation to see the factor of tone, pronunciation, and speech speed in speech recognition. The test was conducted by mentioning the digits 1 through 10. The experimental results showed that the recognition rate for the speech impaired is about 80%, while the recognition rate for normal speech is 100%.